2012
DOI: 10.1017/s0014479712000063
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance in Chickpea as Evaluated by Root Characteristics, Plant Water Status, Membrane Integrity and Chlorophyll Fluorescence Techniques

Abstract: Root traits, such as depth and root biomass, have been identified as the most promising plant traits in chickpea for terminal drought tolerance. With this objective, five contrasting genotypes of chickpea, viz. ICCV-4958, H-208, HC-5, RSG-931 and CSJ-379, having wide adaptability to drought prone areas at national level were assessed for various root characteristics under two environments, i.e. irrigated and rain-fed. The sampling was done at full bloom stage and there were significant differences in the rooti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
12
15
0
Order By: Relevance
“…However, in another experiment within the same study, the yield reduction caused by water stress was less severe, and there was no significant relationship between root length density and seed yield. Similar results were recently obtained in lentils, where root traits and grain yield were not significantly related in a rain-fed situation (Kumar et al 2012). Ratnakumar and Vadez (2011) compared the root systems of 20 groundnut genotypes with variable yields under a range of water stress conditions and showed that the yield differences under stress were not related to differences in rooting depth or root length density at different depths.…”
Section: Usual Assumptions About Roots Under Water-limited Conditionssupporting
confidence: 82%
“…However, in another experiment within the same study, the yield reduction caused by water stress was less severe, and there was no significant relationship between root length density and seed yield. Similar results were recently obtained in lentils, where root traits and grain yield were not significantly related in a rain-fed situation (Kumar et al 2012). Ratnakumar and Vadez (2011) compared the root systems of 20 groundnut genotypes with variable yields under a range of water stress conditions and showed that the yield differences under stress were not related to differences in rooting depth or root length density at different depths.…”
Section: Usual Assumptions About Roots Under Water-limited Conditionssupporting
confidence: 82%
“…The observed significant decrease in RLWC under moisture stressed condition (12 and 10% decrease at 105 DAS during summer and winter) was due to reduced absorption of water from the soil and inability to control water loss through the stomata. Similar results were reported by Kumar et al (2012); Ananthi et al (2013). Among the moisture stress management practices, application of Prosopis biochar+crop residue mulch at 5 t ha -1 +foliar application of PPFM at 500 ml ha -1 at 75 and 90 DAS (B 6 ) recorded higher RLWC (74.7 and 77.3% at 105 DAS) during summer and winter seasons.…”
Section: Relative Leaf Water Contentsupporting
confidence: 85%
“…Relatively lower canopy temperature in drought stressed crop plants indicates a relatively better capacity for taking up soil moisture and for maintaining a relatively better plant water status. The photosynthetic efficiency, transpiration and the values of relative stress injury declined in chickpea under drought conditions [97]. Photosynthetic pigments play an important role in light harvesting and dissipation of excess energy.…”
Section: Relative Stress Injury Ctd and Photochemical Efficiencymentioning
confidence: 99%